EXPANDING HORIZONS: THE ROLE OF KOREAN LANGUAGE IN LANGUAGE FOR SPECIFIC PURPOSES PROGRAMS FOR BUSINESS COMMUNICATION IN ROMANIA - Alexandra Bîja (Journal of Languages for Specific Purposes)
This article examines the possibility of teaching Asian languages—specifically Korean—within the framework of Language for Specific Purposes (LSP) in Romania, particularly for business communication. As Romania’s economic ties with East Asian countries continues to strengthen, there is a growing demand for professionals equipped with both linguistic proficiency and cultural understanding to navigate these partnerships effectively. The article begins with a literature review on LSP, highlighting global trends in Asian language learning and existing research in Romania. It discusses the benefits of cultural competence in business and the competitive advantages that language proficiency can provide in the global market. By proposing a conceptual framework for implementing Korean LSP programs, this article highlights how these initiatives can enhance Romania’s workforce competitiveness, foster deeper business relationships, and strengthen the country’s position in the global economy. The findings aim to serve as a foundation for future empirical research and practical applications in language education.